EFFECT OF LAYERING PATTERN ON MECHANICAL AND WATER ABSORPTION PROPERTIES OF GLASS/FLAX REINFORCED EPOXY (Jurnal Teknologi (Sciences & Engineering), 2017)
In this present study, a new hybrid composite with epoxy as a resin and hybrid reinforcing glass and flax are used  as layered mat. The composites were prepared via vacuum infusion process (VIP) comprising glass and flax fibres with the weight fraction of 57 % and 43 %, respectively. All the laminates were prepared with a total of seven plies, by varying the position of the glass and flax. The effect of stacking sequence of the laminates on the mechanical and physical was characterized by tensile, flexural and water absorption tests. The results indicated that the flexural strength and modulus were significantly dependent on the hybrid configuration in comparison to their tensile properties.  The interplay hybrid laminates with sandwich-like sequence exhibited 10.5 % and 5.5 % higher of flexural strength and modulus, respectively as compared with intercalation. Physical property was observed based on water immersion for 14 days at different elevated temperatures of 40 °C and 80 °C. Result indicated that sandwich-like is better than intercalation sequences for water resistance at both elevated temperatures with the percentage of water intrusion about 4.4 % and 6.35 % at 40 °C and 80 °C, respectively.  Conversely, specimens with  intercalation sequence exhibited 5.1 % and 7.0 % of water intrusion at 40 °C and 80 °C, respectively.